GAS UTILIZATION FROM TIGHT GAS RESERVOIR FOR ELECTRICITY USAGE - WURININGTYAS NIM 22208032, SARITA
Tight gas reservoir is economically not attractive for investors due to its low productivity. Although the production rate is considered low but unconventional reservoir has huge reserves that able to provide long term energy supply. In this study the utilization of gas from tight reservoir as energy consumption for local communities was developed based on tight gas reservoir performance under stimulation and economic aspect. The hydraulic fracturing was considered to improve gas production rate by optimizing fracturing parameters. Economic analysis was done by calculating the all economic parameters that yield company's profits, community benefit and government's role in balancing benefit of both sides. Single well tight gas reservoir unit model was developed based on gas reserves of 10 Bcf which had been stimulated by hydraulic fracturing method using CMG simulator. Optimum hydraulic fracturing designs were obtained by performing sensitivity analysis for formation permeability of 0.001 md - 0.1 md and dimensionless fracture conductivity (CfD) from 1.6 to 70. The optimization of CfD is performed by varying the width of fracture from 0.01 to 0.05 ft and the length of the fracture xf from 100 to 800 ft. The sensitivity results is applied to develop unit model of dry gas reservoir with a permeability of 0.01 md to achieve plateau rate of gas production within two human generations which is about 60 years. The increase in production by optimizing hydraulic fracturing parameters is 2.38 times greater compared to the production of reservoir without hydraulic fracturing. The optimum parameters were fracture width of 0.03 ft and 500 ft fracture half length for CfD equal to 5. Sensitivity was conducted by varying the gas prices, percentage of MARR and average need of electricity per unit household. Economic analysis shows that the utilization of gas from tight gas reservoir to obtain enough electricity for the community allows the selling price of electricity is Rp. 505.00 per kWh. This value based on assumption that electricity demand per household unit per year is 2000 kWh. Using this assumption there would be 8080 household units that able to be supplied for 60 years. Based on this selling price both the company (NPV, IRR and POT) and the community (the purchase price of electricity and the supply time) obtain reasonable profit.